(untitled) (Ta’limning zamonaviy transformatsiyasi, 2024)
Annotation: One crucial ability that has a big impact on the entire learning process is reading comprehension. It gives pupils the ability to interpret data, evaluate information, and apply what they have learned in a variety of subject areas. With a focus on how to improve this crucial ability, this article examines the significance that reading comprehension plays in lifelong learning, cognitive growth, and academic performance.